Student Pathways in South Africa - Schendel, Rebecca (International Higher Education, 2018)
The recent student protests in South Africa highlight a disconnect between academic research on higher education and institutional policy and practice. One reason for this impasse may be the “siloing” of research focused on different “moments” along a student’s pathway through higher education; another is the relative lack of research focused on less-resourced institutions. Addressing these challenges is a priority, not only in South Africa but also around the world.